Guidance for investing in digital health. - Peter,Drury (Metro Manila, Philippines Asian Development Bank, 2018)
Digital technologies are increasingly underpinning almost all aspects of daily life, including health care. The overarching goal is to meet the Sustainable Development Goals, particularly universal health coverage, by investing in digital health. Health care systems have begun to embrace the transformative power of information and communication technology to spur better informed decisions by people and health workers in rural areas and hospitals. Many digital health solutions are already in place, and many are planned. This publication helps identify investments in knowledge, people, policies, and equipment that will maximize the impact of digital health. It presents a digital health impact framework to illustrate how to assess costs, benefits, and timescales; manage expectations; and ensure affordable strategies.
Keywords: Health care reform -- Asia; Technologies and communication; Electronic books